Last decade insights on cemented carbides: A review on alternative binders, new consolidation techniques and advanced characterization - Ravotti, Daniela Andreina Sandoval; Correas, Hortensia Melero; Luis, Núria Cinca (Eclética Química, 2024)
Cemented carbide alloys are well known powder metallurgically processed materials used for a wide range of tooling and components that require a good balance of hardness and fracture toughness, together with wear resistance. After 100 years of the first patent, research and development within this area continues to fulfil more demanding applications and adapt to new requirements. The last decade especially has witnessed important advances. In that sense, Co-free compositions are being studied due to the health issues that its use implies and its criticality in the supply chain. Secondly, the steps towards near-net-shape components by means of additive manufacturing technologies to avoid waste of powder and the technological advance of fast sintering processes are promising. Finally, new microstructural and mechanical characterization methods at micro and nanoscale provide helpful insights for a better understanding of these materials under performance.